Electrochemical reduction of 3‐phenyl‐1, 2‐benzisoxazole 2‐oxide on boron‐doped diamond. (31st January 2014) - Kociolek, Martin; Bennett, Jason; Casbohm, Jerry
<x xml:space="preserve">Abstract</x> The bioreduction of N‐oxide compounds is the basis for the mode of action of a number of biologically active molecules. These compounds are thought to act by forming a reactive oxygen species through an intracellular reduction and subsequent redox cycling process within the organism. With these results in mind, the preliminary investigation into the electrochemical reduction of the benzisoxazole 2‐oxide ring system was undertaken, with the thought that this class of compounds would reduce in a similar fashion to other N‐oxide heterocycles. The electrochemical reduction of 3‐phenyl‐1, 2‐benzisoxazole 2‐oxide on boron‐doped diamond was studied using cyclic and square wave voltammetry as well as controlled potential electrolysis and HPLC for qualitative identification of the reaction products. It was found that the reduction proceeded with an initial quasi‐reversible one‐electron reduction followed by the very fast cleavage of either the endocyclic or exocyclic N–O bond. Subsequent electron transfer and protonation resulted in an overall two‐electron reduction and formation of the 2‐hydroxyaryl oxime and benzisoxazole. These results are analogous to those observed in the electrochemical reduction of other heterocyclic N‐oxides albeit the reduction of the benzisoxazole N‐oxides takes place at a more negative potential. However, these encouraging results warrant further investigation into the reduction potential of substituted benzisoxazole N‐oxides as well as to elucidate and characterize the nature of the intermediate species involved. Copyright © 2014 John Wiley & Sons, Ltd.